Safety and Efficacy of Transarterial Chemoembolization Combined With Immune Checkpoint Inhibitors and Tyrosine Kinase Inhibitors for Hepatocellular Carcinoma - Yang, Fei; Yang, Jun; Xiang, Wei; Zhong, Bin-Yan; Li, Wan-Ci; Shen, Jian; Zhang, Shuai; Yin, Yu; Sun, Hong-Peng; Wang, Wan-Sheng; Zhu, Xiao-Li (Frontiers in Oncology, 2022)
Purpose To explore the safety and efficacy of transarterial chemoembolization (TACE) in combination with Immune checkpoint inhibitors (ICIs) and tyrosine kinase inhibitors (TKIs) in the treatment of unresectable hepatocellular carcinoma (uHCC). Materials and Methods During August 2019 to July 2020, patients who received TACE combined ICIs and TKIs were retrospectively analyzed. treatment related adverse events (AEs) were recorded. Kaplan-Meier method was used to estimate time to progression (TTP), progression free survival (PFS). Results A total of 31 patients with uHCC were included. Eleven patients were classified as BCLC-C. Nineteen patients had multiple lesions, cumulative targeted lesions were 69mm (range, 21-170mm) according to mRECIST. Twenty-nine (93%) patients experienced at least one AEs during the treatment. Four (12.9%) patients developed AEs of higher grade (grade≥3). The objective response rate (ORR) and disease control rate (DCR) was 64.5% and 77.4%, respectively. The median time to response was 7 weeks (range,4-30w) and duration of response was 17.5 weeks (range,2-46w). From first ICIs, TTP and PFS were 6.5 months (95%CI, 3.5-11) and 8.5 months (95%CI, 3.5-NE), respectively. Conclusions TACE combined with ICIs and TKIs show acceptable safety profile and considerable efficacy in patients with HCC.